OC-006 Anti-TNF Therapy Alters Dendritic Cell Trafficking and Cytokine Production in Crohn's Disease. (17th August 2016) - Hendy, PA; Reddi, D; Barnardo, D; Durant, L; Noble, A; Bhat, P; English, N; Knight, SC; Hart, AL
Abstract : Introduction: Dendritic cells (DC) act as a bridge between the innate and adaptive immune system, sensing and presenting antigen to lymphocytes and mounting either a tolerogenic or inflammatory response. They are able to imprint homing capacity on T-cells, directing them into specific tissues. Abnormal DC function contributes to the pathogenesis of Crohn's disease and thus DC represent a potential therapeutic target. In this study we have investigated the effect of anti-TNFα therapy on circulating DC of patients with Crohn's disease. Methods: We recruited 13 consecutive patients with active luminal Crohn's due to start anti-TNFα therapy. Clinical parameters including the Harvey-Bradshaw index, C-reactive protein and faecal calprotectin were measured. Peripheral blood mononuclear cells were isolated from each patient immediately before and six weeks after commencing anti-TNFα therapy. At both time points flow cytometry was performed to assess DC phenotype and function. We also analysed subsets of DC: myeloid (mDC, CD11c + CD123 − ) and plasmacytoid (pDC, CD11c − CD123 + ). Expression of phenotypic markers (including maturation and homing markers and pattern recognition receptors) and intra-cellular on-going DC cytokine production were determined. Results: Treatment with anti-TNFα resulted in an alteration of the phenotype of mDC in Crohn's disease. The gut homing phenotype of mDC in Crohn's disease was down-regulated with anti-TNFα (CLA − β7 + p = 0.0056 Fig A) whilst the non-tissue specific phenotype (CLA + β7 + p = 0.0026 Fig not shown) and skin homing phenotype were up-regulated (CLA + β7 − p = 0.0055 Fig B). Production of TNFα and IL-6 by mDC and pDC respectively, shown to be increased in Crohn's disease, was significantly reduced by anti-TNFα therapy (p = 0.033 and p = 0.014 Fig C and Fig D respectively). Production of IL-10 was increased following therapy (p = 0.051). There were no changes in IL-12, IL-23 and IFN-α production. Significant improvements in clinical markers were observed following treatment. Conclusion: The reversal of inflammatory DC phenotype and function by anti-TNFα further highlights the potential role this antigen presenting cell may play in the pathogenesis of Crohn's disease. DC are a promising therapeutic target in Crohn's because they can be modulated to express a non-gut homing phenotype and direct T cells away from the gut and promote tolerogenic effects. The increase in skin homing DC following anti-TNFα treatment may explain the high rate of skin complications. The reduction in gut homing DC may offer an explanation for reduced treatment success with vedolizumab (α4β7 blocker) after previous anti-TNFα therapy (reduction of vedolizumab treatment target). Disclosure of Interest: None Declared